Tradisi Mengirim Doa Dalam Bentuk Syoko Studi Deskriptif Pada Masyarakat Buddhis di Kabupaten Wonogiri - Situ Asih; Ida Bagus Gde Yudha Triguna (Kamaya: Jurnal Ilmu Agama, 2022)
As a diverse country, Indonesia has various cultures that are believed and carried out for generations. One of the traditions carried out by the Buddhist community in Wonogiri is the tradition of sending prayers to deceased ancestors in the form of Syoko. The Buddhist community believes that the death of a person is not the end of life, so the bereaved family will perform various rituals to pray for the deceased family member. This study aims to describe how the Syoko tradition is carried out and what it means for people who carry out the Syoko tradition. By using a qualitative descriptive method, which was obtained through interviews and direct observation. From the results of the study, it can be explained that the Syoko Tradition carried out by the Buddhist community in Wonogiri has an important meaning. That is sending prayers to ancestors who have died, by sending prayers it is hoped that the living people can help ancestors who have died to go to a happy world of life. The arrangement of the altar which is different from the puja altar in general is that there is a photo of a person who has died in front of the Syoko altar, which aims to help condition the minds of the Buddhist community who praises remembering all the virtues that have been carried out by people who have died while still alive.